Le Grand Voyage: A Great Journey to Liberate Islamic Accounting Education from Utilitarianism and Secularism - Arista Fauzi Kartika Sari; Rahmawati Rahmawati; Harun Al-Rasyid (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
The aim of this study is to release students of Islamic accounting course from secularism and capitalism. This research uses dialogic approach to raise the awareness of criticalmuslim students. The philosophical values of the French movie entitled “Le Grand Voyage” were taken as method of analysis. The reality of Islamic accounting students who are secularist and capitalist was then metaphorized into this film. The results of this study showed that the students could find not only material values, but also emotional values and spiritual values in accounting. There are several values that can be seen from the students’ story telling: material value , altruism value, love value, and spiritual value. It is hoped that this article could give an overview to Islamic accounting educators to provide accounting course accompanied by Islamic substance of tawheed.